2014
DOI: 10.1016/j.apsb.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits the replication of enterovirus 71 in vitro

Abstract: Human enterovirus 71 (EV71) is the main causative pathogen of hand, foot, and mouth disease (HFMD) in children. The epidemic of HFMD has been a public health problem in Asia-Pacific region for decades, and no vaccine and effective antiviral medicine are available. Curcumin has been used as a traditional medicine for centuries to treat a diversity of disorders including viral infections. In this study, we demonstrated that curcumin showed potent antiviral effect again EV71. In Vero cells infected with EV71, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 80 publications
(96 reference statements)
0
51
0
Order By: Relevance
“…Several viruses of the Picornaviridae , Coronaviridae , and Flaviviridae families rely on GBF1 for their replication (Belov et al, ; Carpp, Rogers, Moritz, & Aitchison, ; Goueslain et al, ; Lanke et al, ; Liang, Zheng, Bao, & Zhang, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang, Du, & Jin, ). However, it has been shown that GBF1 is not involved in the formation of poliovirus, mouse hepatitis coronavirus, and HCV replication complexes but rather in their maturation or activity (Belov et al, ; Goueslain et al, ; Verheije et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several viruses of the Picornaviridae , Coronaviridae , and Flaviviridae families rely on GBF1 for their replication (Belov et al, ; Carpp, Rogers, Moritz, & Aitchison, ; Goueslain et al, ; Lanke et al, ; Liang, Zheng, Bao, & Zhang, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang, Du, & Jin, ). However, it has been shown that GBF1 is not involved in the formation of poliovirus, mouse hepatitis coronavirus, and HCV replication complexes but rather in their maturation or activity (Belov et al, ; Goueslain et al, ; Verheije et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…GBF1 also participates in Golgi morphogenesis and lipid droplet metabolism (Jackson & Bouvet, ). In addition, GBF1 is hijacked by several positive‐strand RNA viruses including Picornaviridae , Coronaviridae , and Flaviviridae members for their replication (Belov et al, ; Carpp et al, ; Goueslain et al, ; Lanke et al, ; Liang et al, ; Qin et al, ; van der Linden et al, ; Verheije et al, ; Wang et al, ). For instance, GBF1 was shown to interact with poliovirus and coxsackievirus B3 (CVB3) non‐structural protein 3A (Wessels et al, ; Wessels et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has shown antiviral activity against numerous viruses including dengue virus (serotype 2), human immunodeficiency virus, Japanese encephalitis virus, pseudorabies virus, vaccinia virus, parainfluenza virus type 3 (PIV‐3), feline infectious peritonitis virus (FIPV), vesicular stomatitis virus (VSV), herpes simplex virus (HSV), flock house virus (FHV), respiratory syncytial virus (RSV), hepatitis viruses, influenza type A virus (IAV), Ebola virus, and arthropod‐borne viruses . Different possible mechanisms have been reported for curcumin's antiviral properties such as functioning as an HIV‐1 integrase inhibitor , degrading viral Tat protein , inhibiting proteases , inhibiting viral entry , inhibiting virus attachment to cells , and inhibiting viral replication . Antiviral properties of several metal complexes have been reported .…”
Section: Antiviral Activitymentioning
confidence: 99%
“…We further carefully investigated the inhibition mechanism of the best antiviral agent, Cur‐CQDs‐180, against EV71, although elucidating the exact molecular interactions of the specific functional groups of CQDs and EV71 virions is difficult. Previous studies have demonstrated that antiviral curcumin could interact directly with many proteins, such as DNA polymerase, cell survival proteins, focal adhesion kinase, proteasome, thioredoxin reductase, protein kinase, lipoxygenase, carrier proteins, and tubulin . Therefore, in addition to blocking the viral attachment, the pleiotropic activities of curcumin against viral infection have been demonstrated to emanate from its multiple functions pertaining to a wide range of molecular targets, such as transcription regulation, the activation of intracellular signaling cascades, and the promotion of antioxidative activity.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that curcumin inhibits arthropod‐borne viral infection with Zika and chikungunya viruses by interrupting the binding of viruses on the cell surface . Another study indicated that a high dosage of curcumin exhibited antiapoptotic ability at the early stage of viral infection of EV71 . However, curcumin could not exert a significant effect on the entry of nonenveloped viruses, such as EV71, into host cells, and its antiviral activities were thus limited.…”
Section: Introductionmentioning
confidence: 99%